PENGARUH DIGITALISASI PELAYANAN MELALUI SISTEM INAPORTNET TERHADAP KINERJA OPERASIONAL KAPAL DI PELABUHAN SIWA - Janny Adriani Djari; Indah Indah Nurhidayati; Emi Fitria (UNIMAR AMNI Semarang, 2026)
As a maritime country, Indonesia requires an efficient and integrated port service system to support smooth ship operations and inter-island connectivity. Along with technological developments, the Ministry of Transportation, through the Directorate General of Sea Transportation, has implemented the Inaportnet system as an integrated electronic service for ship clearance processes. However, in its implementation at Siwa Port, the Inaportnet system still faces various technical and non-technical constraints that may affect ship operational performance. Therefore, this study aims to analyse the effect of the implementation of the Inaportnet system on ship operational performance at Siwa Port, particularly in relation to arrival clearance, port stay, and departure clearance. This study employed a quantitative method with an associative approach, with the population and sample consisting of 20 respondents who are directly involved in ship operations and the use of the Inaportnet system at Siwa Port. Data were collected through Likert-scale questionnaires that had been tested for validity and reliability and were analysed using simple linear regression analysis with SPSS version 26. The results indicate that the data are normally distributed and exhibit a linear relationship between variables. The regression analysis and hypothesis testing demonstrate that the implementation of the Inaportnet system has a positive and significant effect on ship operational performance, with a strong level of contribution. Nevertheless, the optimisation of the Inaportnet system implementation still requires support in terms of human resource readiness, the availability of supporting facilities and infrastructure, and system stability. Keywords: Inaportnet, Ship Operational Performance, Port Services, Siwa Port.